Investigating quality education in mother tongue: Ensuring children’s rights to access and equity schooling - Jeilan Aman Gobana (Cogent Education)
Mother-tongue education is an absolute precondition of equitable access to quality education, especially in multilingual settings. Its benefits are well established, yet many education systems continue to systematically marginalize effective mother-tongue instruction, thus denying the rights of linguistically diverse learners. This article investigates the importance of mother-tongue-based education for providing optimum learning environments and children’s rights to inclusive and equitable schooling. It draws theoretical frameworks from Linguistic Human Rights, Interdependence Hypothesis, Critical Pedagogy and Language Planning Orientations to argue eloquently for mother tongue-related considerations within education policy. It argues that learning through a child’s first language enhances performance, promotes cultural identity, and helps in cognitive and socio-emotional development. The article also firmly positions mother-tongue education as essential for upholding children’s linguistic rights, promoting social cohesion, and sustaining cultural diversity. The findings show there is an urgent need to solidify mother-tongue education systems further, as this deliberate policy implementation will be a momentous step towards fostering genuine equity in learning environments where children may thrive and reach their full potential.